Analisis Kinerja Pegawai Sekretariat DPRD Kabupaten/Kota Di Provinsi Riau - YUS, YUSRIADI (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
https://docs.google.com/document/d/1Jpi506apzZTz3iM5cIJagEmYxNjuUDhM/edit?usp=sharing&ouid=103225123065889939204&rtpof=true&sd=true